Postoperative Lung Volume Change Depending on the Resected Lobe - Sengul, Aysen Taslak; Sahin, Bunyamin; Celenk, Cetin; Basoglu, Ahmet (The Thoracic and Cardiovascular Surgeon, 2013)
Objectives The aim of this study was to evaluate the lung volume changes depending on the resected lobes. The changes were quantitatively evaluated using stereological methods on computed tomography images and by pulmonary function tests (PFTs).Methods The study subjects included 30 patients who underwent lung resection. Of these, 26 patients underwent lung resection due to non–small cell lung cancer and 4 patients for benign reasons. Patients were classified into the following six groups according to the resected lobes and lungs: right lower lobectomy, right upper lobectomy, left lower lobectomy, left upper lobectomy, right pneumonectomy, and left pneumonectomy cases. All patients were evaluated with the PFT and computed thorax tomography (CTT), preoperatively and in the postoperative 3rd month. Volume changes due to resection were estimated on CTT scans using the Cavalieri principle of the stereological methods, and their relationships to the PFTs were evaluated.Results Stereologically estimated data showed that the volume loss was 19.01% in upper lobectomy and 5.57% in lower lobectomy (p < 0.05). The highest volumetric increase of the contralateral lung and minor volume loss of the ipsilateral lung was observed in lower lobectomy. After right lower lobectomy, the highest postoperative volume increase was observed at the contralateral lung and the least volume loss in the remaining ipsilateral lung. In PFT, forced vital capacity (FVC) decreased to 3.07% after lower lobectomy whereas it decreased to 11.94% after upper lobectomy. FVC revealed that no significant change occurred after right lower lobectomy (p < 0.05).Conclusions Although the parenchyma resected in lower lobectomy is larger, the postoperative total lung volume reduction is less than that of upper lobectomy. After lower lobectomy, postoperative compensation is achieved specifically by the expansion of contralateral lung, together with the remaining ipsilateral lung.
Keywords: lung resection; stereological method; volume fraction; pulmonary function test; quantity